Impact of alcohol use on thyroid function - Yatan Pal Singh Balhara; Koushik Sinha Deb (Indian Journal of Endocrinology and Metabolism, 2013)
Alcohol is one of the commonest illicit psychoactive substances consumed globally and is the world′s third largest risk factor for disease and disability. It has been reported to have multiple effects on the hypothalamo-pituitary-thyroid axis and the functioning of the thyroid gland. It has been reported to cause direct suppression of thyroid function by cellular toxicity, and indirect suppression by blunting thyrotropin-releasing hormone response. It causes a decrease of peripheral thyroid hormones during chronic use and in withdrawal. Alcohol use may also confer some protective effect against thyroid nodularity, goiter, and thyroid cancer. This article presents a review of the clinically relevant effects of alcohol on the functioning of the thyroid gland and also discusses the effect of medication used in treatment of alcohol dependence on thyroid function.